Characteristics of fluorine-doped tin oxide thirf films on poly ethylene terephthalate (PET) substrate - Kook, Yun Ho; Park, Ji Hun; Byun, Dong Jin; Lee, Joong Kee (ECO-MATERIALS PROCESSING AND DESIGN VIII, 2007)
Fluorine-doped tin oxide (FTO) films on PET (Polyethylene Terephthalate) substrate were prepared by the electron cyclotron resonance-metal organic chemical vapor deposition (ECR-MOCVD) under an Ar-O-2-H-2 atmosphere. The used tin and fluorine precursor are TMT (tetramethyltin) and sulfur hexafluoride (SF6), respectively. The hydrogen content plays an important role to control the optical and electrical characteristics of the films. The HF etching effect was clearly observed with increase of H-2/TMT mole ratio, on the other hand the hydro-carbon deposition increased with decrease of H-2/TMT mole ratio. Therefore the optimum H-2 content can be determined by the counter balance effect between HF etching and hydro-carbon deposition. The obtained optimum SnO2: F thin films exhibited over 90% of optical transmittance at wavelength range from 380 to 780 nm and c.a. 6x10(-3) ohm cm of electrical resistivity at 1.25 H-2/TMT mole ratio.